Comparative proteomic analysis of human embryonic stem cell-derived and primary human retinal pigment epithelium - Heidi Hongisto (Nature Portfolio, 2017)
Abstract Human embryonic stem cell-derived retinal pigment epithelial cells (hESC-RPE) provide an unlimited cell source for retinal cell replacement therapies. Clinical trials using hESC-RPE to treat diseases such as age-related macular degeneration (AMD) are currently underway. Human ESC-RPE cells have been thoroughly characterized at the gene level but their protein expression profile has not been studied at larger scale. In this study, proteomic analysis was used to compare hESC-RPE cells differentiated from two independent hESC lines, to primary human RPE (hRPE) using Isobaric tags for relative quantitation (iTRAQ). 1041 common proteins were present in both hESC-RPE cells and native hRPE with majority of the proteins similarly regulated. The hESC-RPE proteome reflected that of normal hRPE with a large number of metabolic, mitochondrial, cytoskeletal, and transport proteins expressed. No signs of increased stress, apoptosis, immune response, proliferation, or retinal degeneration related changes were noted in hESC-RPE, while important RPE specific proteins involved in key RPE functions such as visual cycle and phagocytosis, could be detected in the hESC-RPE. Overall, the results indicated that the proteome of the hESC-RPE cells closely resembled that of their native counterparts.